Alley Cropping System for Soil Resource Management - Burman, D.; Gill, A.S. (Indian Journal of Agroforestry, 2020)
The potentially arable land resources are limited and not sufficient to meet the needs of the projected human and animal population. Moreover, considerable amounts of land are degraded every year. The suitable cropping systems are to be followed to enhance the soil quality. The alley cropping is a potential system for improving soil health. In this paper the concepts of alley cropping, its benefits, potentials, limitations and opportunities for sustainable management of soil resources are discussed.